HUBUNGAN ANTARA BUDAYA KELAS BERSIH DAN INTERNALISASI NILAI-NILAI KEISLAMAN SISWA DI MTS AL-IKHLAS PROKLAMASI KARAWANG - Fadila Amelia; Debibik Nabilatul Fauziah; Neng Ulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of clean classroom culture, the level of internalization of Islamic values ​​​​of students, and the relationship between clean classroom culture and internalization of Islamic values ​​​​at MTs Al-Ikhlas Proklamasi Karawang. The study used a quantitative approach with a correlational method. The study population was 341 students and a sample of 77 students determined using the Slovin formula with a proportional sampling technique. Data collection was carried out through questionnaires, observation, and documentation. Data were analyzed using descriptive statistics and Pearson Product Moment correlation after meeting the normality and linearity tests. The results showed that the clean classroom culture was in the medium category with an average value of 59.07, while the internalization of Islamic values ​​​​was in the medium category with an average value of 61.76. The results of the Pearson Product Moment correlation test showed a correlation coefficient value of 0.759 with a significance value <0.05. This study shows a positive and significant relationship between a clean classroom culture and students' internalization of Islamic values. The greater the students' participation in a clean classroom culture, the higher the level of internalization of Islamic values. A clean classroom culture can be an effective means of instilling the values ​​of cleanliness, responsibility, discipline, cooperation, and environmental awareness as part of Islamic values.